Virulence Profiles, Phylogenetic Background, and Antibiotic Resistance of Escherichia coli Isolated from Turkeys with Airsacculitis - Marcos Paulo Vieira Cunha; Maria Gabriela Xavier de Oliveira; Mirela Caroline Vilela de Oliveira; Ketrin Cristina da Silva; Cleise Ribeiro Gomes; Andrea Micke Moreno; Terezinha Knöbl (The Scientific World Journal)
Avian Pathogenic Escherichia coli (APEC) has been studied for decades because of its economic impact on the poultry industry. Recently, the zoonotic potential of APEC and multidrug-resistant strains have emerged. The aim of this study was to characterize 225 APEC isolated from turkeys presenting airsacculitis. The results showed that 92% of strains presented a multidrug-resistance (MDR), and the highest levels of resistance were to sulfamethazine (94%) and tetracycline (83%). Half of these strains were classified in phylogenetic group B2, followed by B1 (28.6%), A (17.1%), and D (4.8%). The prevalence of virulence genes was as follows: salmochelin (iroN, 95%), increased serum survival (iss, 93%), colicin V (cvi/cva, 67%), aerobactin (iucD, 67%), temperature-sensitive haemagglutinin (tsh, 56%), iron-repressible protein (irp2, 51%), invasion brain endothelium (ibeA, 31%), vacuolating autotransporter toxin (vat, 24%), K1 antigen (neuS, 19%), enteroaggregative heat-stable cytotoxin (astA, 17%), and pilus associated with pyelonephritis (papC, 15%). These results demonstrate that the majority of the investigated strains belonged to group B2 and were MDR. These data suggest that turkeys may serve as a reservoir of pathogenic and multidrug-resistance strains, reinforcing the idea that poultry plays a role in the epidemiological chain of ExPEC.